Adjuvant gemcitabine plus cisplatin versus capecitabine in node-positive extrahepatic cholangiocarcinoma: the STAMP randomized trial. Issue 5 (3rd May 2023) - Jeong, Hyehyun; Kim, Kyu-pyo; Jeong, Jae Ho; Hwang, Dae Wook; Lee, Jae Hoon; Kim, Ki-Hun; Moon, Deok-Bog; Lee, Myung Ah; Park, Se Jun; Chon, Hong Jae; Park, Jin-hong; Lee, Ji Sung; et al.
Abstract : Abstract : Background and Aims: The effectiveness of gemcitabine-based adjuvant chemotherapy is unclear in cholangiocarcinoma. We investigated the role of adjuvant gemcitabine plus cisplatin (GemCis) in a homogeneous group of high-risk patients with resected, lymph node–positive extrahepatic cholangiocarcinoma. Approach and Results: Adenocarcinoma of perihilar or distal bile duct with regional lymph node metastasis who underwent curative-intent surgery (R0/R1) was eligible. Patients were randomized to receive GemCis (gemcitabine 1000 mg/m 2, cisplatin 25 mg/m 2 on days 1 and 8) or capecitabine (1250 mg/m 2 twice daily on days 1–14) every 3 weeks for 8 cycles. Primary endpoint was disease-free survival. Secondary endpoints were overall survival and safety. All p values are 1 sided and were considered significant if <0.1. Between July 2017 and November 2020, 101 patients (50 in the GemCis and 51 in the capecitabine group) were included in the intention-to-treat population. Perihilar and distal bile ducts were the primary sites in 45 (44.6%) and 56 (55.4%) patients, respectively, and 32 (31.7%) had R1 resections. Median (1-sided 90% CI) follow-up duration was 33.4 (30.5–35.8) months. In the GemCis and capecitabine group, 2-year disease-free survival rates were 38.5% (29.5%–47.4%) and 25.1% (17.4%–33.5%) [HR=0.96 (CI, 0.71–1.30), p =0.430], and median overall survival was 35.7 months (29.5–not estimated) and 35.7 months (30.9–not estimated) [HR=1.08 (CI, 0.71–1.64), 1-sided p =0.404], respectively. Grade 3–4 adverse events occurred in 42 (84.0%) and 8 patients (16.0%) in the GemCis and capecitabine groups, respectively. No treatment-related deaths were reported. Conclusions: In resected lymph node–positive extrahepatic cholangiocarcinoma, adjuvant GemCis did not improve survival outcomes compared with capecitabine.